AN INVESTIGATION OF SELF-CONCEPTS AND MOTIVATION OF STUDENTS ON DIFFERENT TEACHING METHODS IN G.C.E. (O/L) PHYSICS - Maheshinee, S.A.B.; Chandrasena, W.D.; Liyanage, J.P. (International Journal of Research -GRANTHAALAYAH, 2019)
Science education is a valuable asset to gain scientific knowledge and share it within the community. Some students’ performances in physics are not very satisfactory. Thus, the purpose of this study was to investigate the relations of G.C.E. (O/L) students’ science self concepts, motivation with the teaching methods in the lessons on forces in Grade 10. The four different teaching methods used for this study were included problem based learning; practical based learning, cooperative learning, and integrated learning. This study was conducted in an educational zone in the North Western Province, Sri Lanka. A convenience sample of 185 Grade 10 students and 5 teachers participated in the study. The quantitative data were collected using a pre test paper, physics self-concepts scale, physics motivation scale and a final assessment test paper. Qualitative data were collected in Grade 10 students to explore their views on different teaching methodology. Quantitative data were analyzed using SPSS 17.0. Qualitative data were analyzed using thematic analysis. The results revealed that students’ self concepts and motivation were highest in the integrated teaching method while the lowest was problem based. However, practical approach was highly admired by the students and teachers to learn forces lesson. The findings of this study could be used in planning forces lessons in Grade 10.